m(m-6)(2m+3)=0

Simple and best practice solution for m(m-6)(2m+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m(m-6)(2m+3)=0 equation:


Simplifying
m(m + -6)(2m + 3) = 0

Reorder the terms:
m(-6 + m)(2m + 3) = 0

Reorder the terms:
m(-6 + m)(3 + 2m) = 0

Multiply (-6 + m) * (3 + 2m)
m(-6(3 + 2m) + m(3 + 2m)) = 0
m((3 * -6 + 2m * -6) + m(3 + 2m)) = 0
m((-18 + -12m) + m(3 + 2m)) = 0
m(-18 + -12m + (3 * m + 2m * m)) = 0
m(-18 + -12m + (3m + 2m2)) = 0

Combine like terms: -12m + 3m = -9m
m(-18 + -9m + 2m2) = 0
(-18 * m + -9m * m + 2m2 * m) = 0
(-18m + -9m2 + 2m3) = 0

Solving
-18m + -9m2 + 2m3 = 0

Solving for variable 'm'.

Factor out the Greatest Common Factor (GCF), 'm'.
m(-18 + -9m + 2m2) = 0

Factor a trinomial.
m((-3 + -2m)(6 + -1m)) = 0

Subproblem 1

Set the factor 'm' equal to zero and attempt to solve: Simplifying m = 0 Solving m = 0 Move all terms containing m to the left, all other terms to the right. Simplifying m = 0

Subproblem 2

Set the factor '(-3 + -2m)' equal to zero and attempt to solve: Simplifying -3 + -2m = 0 Solving -3 + -2m = 0 Move all terms containing m to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2m = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2m = 0 + 3 -2m = 0 + 3 Combine like terms: 0 + 3 = 3 -2m = 3 Divide each side by '-2'. m = -1.5 Simplifying m = -1.5

Subproblem 3

Set the factor '(6 + -1m)' equal to zero and attempt to solve: Simplifying 6 + -1m = 0 Solving 6 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1m = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1m = 0 + -6 -1m = 0 + -6 Combine like terms: 0 + -6 = -6 -1m = -6 Divide each side by '-1'. m = 6 Simplifying m = 6

Solution

m = {0, -1.5, 6}

See similar equations:

| 2a^2+22a+60=0 | | b=8cmh | | s=7.15+.35s | | 0.2b+3=0.5b+12 | | s=7.15+.35x | | 3x-22=14 | | 6y^2-13y+5=0 | | .7(4x+.3)=41.65 | | 2y^2+3y-5=0 | | [3-(5+3*2)]-3= | | -2(v-7)=-7+44 | | .58n-.86=4.592 | | 6g+4(-3+3g)=1-g | | 2x^2+10x=-16 | | 6(4x-2)=12 | | 1/12(48+24b)=2(17-4b) | | 6g+4(-3+g)=1-g | | -4x+9x=30 | | 125-85= | | 7-7x=21+3x | | (6x-15)=(2x+5) | | 7-n=21+3-n | | 2x^2+16x-66=0 | | -3+9b=96 | | 2x^2-1=1 | | -X^2+2x-6=0 | | 189=-1+10m | | (a)+(3a)+(18a-6)=180 | | 15y=6x-15 | | 2x^2-1=8 | | 15=15y+6x | | (a)+(3a)+(18a-6)=180(given) |

Equations solver categories